Annual Report of the Librarian of Congress - United States Government printing office, Washington, DC.; Library of Congress, Washington, DC. (Washington, D.C. : United States Government printing office, 1941)
Following the introduction which gives an overall picture of developments in the Library of Congress, the chapters deal specifically with the: (1) processing department, (2) legislative reference service, (3) reference department, (4) law library, (5) administrative department and (6) copyright office. The 14 appendices show, in a figurative sense, the growth of the Library of Congress collections and many of its operations. The index is a merged listing by subject and author in alphabetical order. (NH)
Microfiche.
Keywords: Annual Reports; Library Technical Processes; Reference Services; Government Libraries; Library Collections; Library Services; National Libraries; Library of Congress